O caráter oracular da mídia - Moreira, Nádia Maria Lebedev Martinez (2015)
The research aim to establish a direct relationship between its subjects, the Oracle and the Media. The main hypothesis is that the media has an oracular character. This reflection seems to be new within the Media Theory studies, and speculates that the future has a present event status. The oracles, or oracular character figures, when performing their predictions, design the future in the present, building scenarios that guide both the individual in his private life, as the society as a whole. The adopted methodological strategy sought to develop an archeology of the oracles in the West - especially the Oracle of Delphi, given its importance to the emergence of Western civilization and its institutions, including the media itself understanding them as backers of information, also a defining characteristic of the media. Researches concepts proposed by the Theory of Media in the reflections of Norval Baitello, Harry Pross and Flusser. Anxiety about the future is read from Soren Kierkegaard and Carl Gustav Jung. Within the concept of cultural anxiety Rafael Lopez-Pedraza, thinks the relationship of individuals and society in the future, this relationship also studied by Julian Jaynes in his deconstruction of the bicameral mind. Also Norbert Elias, who investigates what he calls a society of individuals. The hypothesis is tested trough media examples that analyze topics such as the economic crisis brought by the US housing bubble; Brazilian water crisis in 2015; and predictions about games results in sporting championships